Clinical and socio-demographic correlates of anxious distress in Asian outpatients with major depressive disorder - Maneeton N. (2017)
© 2017 The Nordic Psychiatric Association. Background: Anxious distress in major depressive disorder (MDD) is common and associated with poor outcomes and management difficulties. Aims: This post hoc analysis aimed to examine the socio-demographic and clinical correlates of anxiety distress in Asian outpatients with MDD. Methods: Instead of two out of five specifiers defined by the Diagnostic and Statistical Manual Version-5, anxious distress defined in this study was operationalized as the presence of at least two out of four proxy items drawn from the 90-item Symptom Checklist, Revised (SCL-90-R). Other measures included the Montgomery–Asberg Depression Rating Scale (MADRS), the Fatigue Severity Scale, the Sheehan Disability Scale and the Multidimensional Scale of Perceived Social Support. Results: The data of 496 patients with MDD were included. Anxious distress was found in 371 participants (74.8%). The binary logistic regression analysis found that anxious distress was independently and significantly correlated with working status, higher MADRS scores, severe insomnia and functional impairment. Conclusions: Three-fourths of Asian patients with MDD in tertiary care settings may have DSM-5 anxious distress of at least moderate distress. Its prevalence may vary among working groups. The specifier was associated with greater depressive symptom severity, severe insomnia and functional impairment.